2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.182
|View full text |Cite
|
Sign up to set email alerts
|

Does Culture Interact with Media Richness? The Effects of Audio vs. Video Conferencing on Chinese and American Dyads

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In a CMC setting with reduced cues for ethnicity, we expect incongruent conditions to lead to confusion and misattribution. If a student's name does not indicate a foreign cultural background, an indirect communication style may be interpreted as strange (Choy & Dodd, 1976;Lev-Ari & Keysar, 2010;Setlock, Fussell, & Neuworth, 2004;Setlock, Quinones, & Fussell, 2007). This raises the probability that the fundamental attribution error will occur (Ross, 1977).…”
Section: Hypothesesmentioning
confidence: 99%
“…In a CMC setting with reduced cues for ethnicity, we expect incongruent conditions to lead to confusion and misattribution. If a student's name does not indicate a foreign cultural background, an indirect communication style may be interpreted as strange (Choy & Dodd, 1976;Lev-Ari & Keysar, 2010;Setlock, Fussell, & Neuworth, 2004;Setlock, Quinones, & Fussell, 2007). This raises the probability that the fundamental attribution error will occur (Ross, 1977).…”
Section: Hypothesesmentioning
confidence: 99%
“…Previous studies of culture and CMC have typically used tasks such as direction-giving [12] [45] or rank ordering items [38] [40] that have, at least in principle, one correct solution. Group brainstorming differs from such tasks along a number of dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Richer media such as video conferencing have more of these features than leaner media such as Instant Messaging. In a study comparing the effects of media richness for the interpersonal communication between high-context Chinese dyads and low-context American dyads, there were few cultural differences found [17]. But it was concluded that for the Chinese pairs, visual awareness was significantly more socially fulfilling than for the low-context pairs because of the availability of high-context information.…”
Section: Culture and Computer-mediated Communicationmentioning
confidence: 99%
“…In recent years, there has been a growing interest in studies examining cultural issues in CMC [10,17,18]. An analysis of this field concluded that it is hard to identify explanatory themes or frameworks, and often contrary results are yielded [19].…”
Section: Culture and Computer-mediated Communicationmentioning
confidence: 99%
See 1 more Smart Citation